L’Agriculture, l’État et la stagflation mondiale : la politique canadienne depuis 1970 - Ehrensaft, Philip (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The development of Canadian agriculture was founded (similarly to that of Australia, New Zealand, Argentina and Uruguay) on the basis of an economy with dominion-wide referents. To begin, this article ascertains the general characteristics of that System. It then considers the System 's evolution in Canada since 1970. The increase in the world prices of energy (of which Canada is a net exporter) and the reorganization of the national transportation network are altering the roles of the different provinces with regard to agricultural production and are leading to a dismantling of the Boards, which were until now the only intermediary with foreign markets. Ultimately these trends point to an overall reorganization of the Canadian agricultural System.